Penerapan Teknologi Big Data Dalam Pengembangan Database Pendidikan - Veri Ferdiansyah; Muhammad Irwan Padli Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Big data is a new and important technological development that allows storage and integration of very large volumes of data from various sources. Regardless of location, you can use secure, easy and timely data thanks to this technology. The Covid-19 pandemic has made the use of distance learning very important. To collect information and data in this study, which used a qualitative methodology with a literature review approach, information and data were collected from various sources in the library, including books, scientific papers, magazines, historical records, and others. The purpose of this research is to understand how big data is used in online education in general and in Indonesia. The findings of this study, based on literature and media sources, indicate that the use of big data in education has not gained wide acceptance. Therefore, policy makers have the opportunity to provide guidance to educational institutions in implementing big data for distance learning. However, there are also obstacles in implementing big data for distance learning, such as differences in data rates in various regions in Indonesia, which require efforts to accelerate the implementation of big data in each region.